2020
DOI: 10.3390/app10228084
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Primary and Secondary Implant Stability—A Retrospective Cohort Study with 582 Implants in 272 Patients

Abstract: The success rate of dental implants depends on primary and secondary stability. We investigate predictive factors for future risk stratification models. We retrospectively analyze 272 patients with a total of 582 implants. Implant stability is measured with resonance frequency analysis and evaluated based on the implant stability quotient (ISQ). A linear regression model with regression coefficients (reg. coeff.) and its 95% confidence interval (95% CI) is applied to assess predictive factors for implant stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…In the present study, the implant diameter proved to be an influential factor, where lower stability was recorded in DIs with a narrower diameter which is in line with other studies (19) . Whereas other investigators found significant relation between implant diameter and primary stability only, (18,25,26) others found the significant effect was on secondary stability only (27) . Analyzing the effect of DI length on implant stability revealed that there was no significant relation between implant length and stability throughout the study period.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the present study, the implant diameter proved to be an influential factor, where lower stability was recorded in DIs with a narrower diameter which is in line with other studies (19) . Whereas other investigators found significant relation between implant diameter and primary stability only, (18,25,26) others found the significant effect was on secondary stability only (27) . Analyzing the effect of DI length on implant stability revealed that there was no significant relation between implant length and stability throughout the study period.…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, the recipient jaw had no significant effect on ISQ values except for the primary stability, where maxillary implants demonstrated higher stability, however, on examining the data, it can be observed that DIs inserted in the mandible maintained better stability during the early postoperative period obtaining a mean difference of -1.3 ISQ values compared to that of the maxillary DIs that was much higher (-5.8 ISQ values). Vollmer et al (18) observed a positive association between primary implant stability and localization (mandibular vs. maxillary), although, the authors reported an increased ISQ values between insertion and exposure (secondary stability) which was significantly correlated with healing time and was higher in the maxilla. The ISQ values of the secondary stability and after functional loading were higher for all DIs in comparison to ISQ0 and ISQ8 irrespective to the recipient jaw.…”
Section: Discussionmentioning
confidence: 96%
“…With the introduction of resonance frequency analysis in the 1990s, primary and secondary implant stability measurements became feasible [36][37][38]. Whereas primary implant stability depends on bone morphology and implant characteristics, secondary implant stability considers the physiological tissue response to the implant and subsequent bone remodeling processes, indicating successful osseointegration and implant success [39,40]. The output of the implant stability measurements can be evaluated via the implant stability quotient (ISQ) and should be ≥ 60 to assume sufficient implant stability [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Since the inception of current implant designs, modifications to improve osseointegration have led to reportedly [4][5][6] favorable implant survival rates for partially edentulous and edentulous patients. Dental implant osseointegration results through the primary stability as influenced by the bone quantity and quality at the implant site through clinical and biological steps [7,8]. Further modifications of the implant surface to enhance bone growth and maintenance are important for initial healing and ongoing implant stability in function.…”
Section: Introductionmentioning
confidence: 99%